Effect of progressive bridging exercise on weight-bearing during the extension phase of sit-to-stand, and on sit-to-stand ability in individuals with stroke: A randomised controlled trial. (November 2022) - Pankheaw, Thitinat; Hiengkaew, Vimonwan; Bovonsunthonchai, Sunee; Tretriluxana, Jarugool
Objective: To examine the effect of a progressive bridging exercise on force, time, and pressure during the extension phase of sit-to-stand, and on sit-to-stand ability in individuals with stroke. Design: A single-blinded randomised controlled trial. Setting: Hospital. Participants: Forty-eight individuals with acute ischemic stroke, not at brainstem and cerebellum, randomly allocated to the intervention ( n  = 24) and control ( n  = 24) groups. Five participants dropped out during the 2-month follow-up, but they were in the intention-to-treat analysis. Interventions : The intervention group undertook a 45-min conventional physiotherapy and a 30-min progressive bridging exercise. The control group received only the conventional exercise. Main measures: Peak vertical ground reaction force, time to peak force, peak foot pressure, and regional peak foot pressure during the extension phase of sit-to-stand, and sitting-to-standing item of the Motor Assessment Scale were assessed before training, after 4-week training, and 2-month follow-up. Results: The intervention group showed significantly ( p  < 0.001) less difference in peak vertical ground reaction force between feet during the extension phase of sit-to-stand than the control after 4-week training (mean ± standard deviation; intervention, 5.38 ± 3.99; control, 17.1 ± 10.3) and 2-month follow-up (intervention, 6.79 ± 3.84; control, 17.5 ± 9.89), and demonstrated significantly ( p  < 0.001) higher score in sit-to-stand than the control after training [mean (interquartile range); intervention, 5 (2-5); control, 2 (1-2)] and follow-up [intervention, 2 (2-5); control, 2 (1-2)]. Both groups demonstrated peak foot pressure on the medial and lateral heels, metatarsals, and hallux regions. Conclusion : Progressive bridging exercise improved symmetrical weight bearing during the extension phase of sit-to-stand, consequently enhanced sit-to-stand ability in individuals with stroke.